Numerical Simulation on the Solute Concentration Distribution in Sapphire Crystals During Czochralski Growth Method - Nguyen, Nguyễn Trần Phú (Journal of Technical Education Science, 2024)
In this study, the flow, temperature and solute concentration distributions in the melt during the CZ growth process are numerically investigated. The results show that the magnitude and distribution of the solute concentration in the melt is strongly affected by the convective flow and the thermal distribution, since both Prandtl and Schmidt numbers are very high. The buoyancy convection forms a vortex within the melt, flowing up at the sidewall and down at the centerline. When the chemical reaction between the alumina oxide and the tungsten crucible wall is taken into account, the maximum tungsten trioxide concentration always occurs at the crucible sidewall where the maximum temperature in the melt is found and its concentration at the crystal-melt interface increases from the triple point to the centerline. When the graphite effect is considered, the maximum carbon concentration always occurs at the free surface of the melt closed to the crucible sidewall and the carbon concentration at the crystal-melt interface decreases from the triple point to the centerline of crystal.